2016
DOI: 10.3791/54693
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of Circulating miRNAs in Irritable Bowel Syndrome Detected Using a Multiplexed High-throughput Gene Expression Platform

Abstract: The gene expression platform assay allows for robust and highly reproducible quantification of the expression of up to 800 transcripts (mRNA or miRNAs) in a single reaction. The miRNA assay counts transcripts by directly imaging and digitally counting miRNA molecules that are labeled with color-coded fluorescent barcoded probe sets (a reporter probe and a capture probe). Barcodes are hybridized directly to mature miRNAs that have been elongated by ligating a unique oligonucleotide tag (miRtag) to the 3' end. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Emerging evidence has pointed out the involvement of miRNAs in modulating specific biological processes in IBS-D, which may be translated clinically to restore intestinal functions and alleviate gastrointestinal symptoms (17,18). This present study revealed that miR-16 was under-expressed in the IBS-D patients and mouse model.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 55%
“…Emerging evidence has pointed out the involvement of miRNAs in modulating specific biological processes in IBS-D, which may be translated clinically to restore intestinal functions and alleviate gastrointestinal symptoms (17,18). This present study revealed that miR-16 was under-expressed in the IBS-D patients and mouse model.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 55%
“…Previous studies have identified miRNAs such as miR-29a/b, miR-24, miR-510, miR-212, miR-150, miR-342-3p, miR-199a, miR-125b-5p, miR-16, miR-144, miR-200a, miR-214, and miR-103 as potential therapeutic targets for IBS [ 80 , 81 ]. Simultaneously, some differentially expressed miRNAs have contributed to the diagnosis of different IBS subtypes [ 82 ]. Variations in transcriptomic profiles based on mRNA and miRNA may help distinguish UC from IBS [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, some differentially expressed miRNAs have contributed to the diagnosis of different IBS subtypes [ 82 ]. Variations in transcriptomic profiles based on mRNA and miRNA may help distinguish UC from IBS [ 82 ]. Additionally, miRNA therapy has several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several miRNAs (miR-663b, miR-342, etc.) could be used to precisely distinguish the different subtypes of IBS ( 44 , 45 ). miRNAs exert a critical role in intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%